Changes in Korean wage inequality, 1980-2005 - Byung-goo Kang; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2008)
Korea is known not only for rapid economic growth but also relatively low wage inequality. It is one of the few countries in which wage inequality decreased during the 1980s, though in recent years wage inequality has increased. This paper studies what factors contributed to the changes in wage inequality during the last two decades. This paper implements a recently developed Oaxaca-type inequality decomposition method to decompose U shaped changes in inequality into characteristics (quantity), coefficients (price) and residuals effects at both overall and detailed levels. The results of decomposition analysis show that changes in the wage structure significantly contribute to the changes in wage inequality in Korea. The coefficients effect of human capital factors has played a major role not only in increasing wage inequality from mid-1990s, but also decreasing wage inequality in 1980s and early 1990s.
urn:nbn:de:101:1-20081126399
Keywords: D30; 330; Decomposition analysis of inequality; earnings equation; coefficients (price) effect; characteristics (quantity) effect; residuals effect; Lohnstruktur; Soziale Ungleichheit; Humankapital; Dekompositionsverfahren; Südkorea